2010
DOI: 10.1073/pnas.0805532107
|View full text |Cite
|
Sign up to set email alerts
|

Delivery of foreign antigens by engineered outer membrane vesicle vaccines

Abstract: As new disease threats arise and existing pathogens grow resistant to conventional interventions, attention increasingly focuses on the development of vaccines to induce protective immune responses. Given their admirable safety records, protein subunit vaccines are attractive for widespread immunization, but their disadvantages include poor immunogenicity and expensive manufacture. We show here that engineered Escherichia coli outer membrane vesicles (OMVs) are an easily purified vaccine-delivery system capabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
258
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 256 publications
(265 citation statements)
references
References 46 publications
6
258
0
1
Order By: Relevance
“…ClyA toxin is also believed to follow a similar strategy when attacking host cells (1). However, unlike the well-studied ␤-toxins ␣-hemolysin and protective antigen from anthrax toxin, which are secreted by Gram-positive bacteria into the extracellular environment as a soluble monomer (19,20), ClyA is secreted from E. coli via a vesicle-mediated pathway (21)(22)(23). Similar to the budding of yeast cells, the outer membrane of E. coli bubbles out and pinches off to form the outer membrane vesicles (OMVs) (24).…”
mentioning
confidence: 99%
“…ClyA toxin is also believed to follow a similar strategy when attacking host cells (1). However, unlike the well-studied ␤-toxins ␣-hemolysin and protective antigen from anthrax toxin, which are secreted by Gram-positive bacteria into the extracellular environment as a soluble monomer (19,20), ClyA is secreted from E. coli via a vesicle-mediated pathway (21)(22)(23). Similar to the budding of yeast cells, the outer membrane of E. coli bubbles out and pinches off to form the outer membrane vesicles (OMVs) (24).…”
mentioning
confidence: 99%
“…route elicits an antibody response that significantly reduces small-intestinal colonization of suckling neonates challenged orally with V. cholerae (71). In addition, by using OMVs as a delivery vehicle, responses to heterologous antigens have been observed with mice without the need for additional adjuvants (22,70). Therefore, OMVs may represent a versatile vaccine delivery system with natural mucosal adjuvant properties.…”
mentioning
confidence: 99%
“…The anti-GFP humoral response in mice immunized with the engineered OMV formulations was indistinguishable from the response to the purified ClyA-GFP fusion protein alone and was equal to the response to purified proteins adsorbed to aluminum hydroxide, a standard adjuvant. Engineered OMVs containing ClyA-GFP were easily isolated by ultracentrifugation, thus effectively eliminating the need for a laborious antigen purification from cell-culture expression systems (Chena et al, 2010). The retention of hemolytic-protein activity indicated that ClyA-antigen fusions maintained their conformations.…”
Section: Vaccinesmentioning
confidence: 99%